ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN PELANGGAN PADA PT. TELEKOMUNIKASI, TBK. MAKASSAR - Sardjan, Baso; Hasliah, Hasliah; Nurhaedah, Nurhaedah (Patria Artha Management Journal, 2022)
The research aims to determine the effect of reliability, guarantees (assurance), physical evidence (tangible). Communication (euphy), response tocustumer satisfactian at Pt Telekomication Tbk Makassar in research using quantitaive researrch methods. The result of this study from the variables used in the good category.This means that customers are satisfied with the traetment of employes against violations, convenience in the services provided by PT Telekomunication and employess always give greetings to violatons are good. Of the 4 Variables used in terms of reliability categories are quite good. This means that the custumers felt to the provision of information about the product and service on time is not optimal so that the company must be able to increase the reliability of employess in providing services. Knowledge of employess in the product shows research is included in the very goog category and this means employees are able to explain to violations of each product that is in the company